EFFECTIVENESS OF DIFFERENT TRAINING MODES IN THE TRANSFER OF MINERAL MIXTURE FEEDING TECHNOLOGY AMONG DAIRY FARMERS - P. Mathialagan; P.R. Nisha; N. Vimal Rajkumar; S. Saraswathi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present study was conducted on 100 dairy farmers selected from four villages of Vellore district of Tamilnadu to ascertain the effectiveness of different training modes for transfer of mineral mixture feeding technology. Gain in knowledge was evident in the sub domains viz., quality of ingredient, preparation of concentrates, storage and feeding of concentrates. There was a significant gain in knowledge of the respondents who taught with the help of short- films than other modes and the calculated t"value was greater than tabulated and found significant. Therefore, it can be concluded that short- films had increased the knowledge of rural farmers.